New taxonomic combinations in West Indian Ocean Vanguerieae (Rubiaceae) - Kainulainen, Kent; Razafimandimbison, Sylvain G. (Phytotaxa, 2016)
This paper provides new combinations for two species endemic to the Seychelles, Canthium carinatum and C. sechellarum, which are transferred to Peponidium (tribe Vanguerieae, Ixoroideae, Rubiaceae), as supported by recent molecular phylogenetic analyses. Several new combinations in Vanguerieae from Madagascar are also proposed, based on morphological studies. Canthium bakerianum and C. homolleanum are transferred to Peponidium, whereas C. andringitrense, C. mandrarense, and Peponidium montana are transferred to Pyrostria. The names Pyrostria angustifolia, P. media, and P. major, previously invalid, are here validly published.